2017
DOI: 10.1166/jbn.2017.2353
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Anticancer Drugs (5-Fluorouracil and Paclitaxel) into Polycaprolactone (PCL) Nanofibers and In Vitro Testing for Sustained and Targeted Therapy

Abstract: We report a continuous nanoscale encapsulation of cancer drugs 5-Fluorouracil (FU) and Paclitaxel into biocompatible polycaprolactone (PCL) nanofibers (NFs) using core-sheath electrospinning process. A high potential electric field of 19–23.2 kV was used to draw a compound solution jet from a specialized coaxial spinneret. Using of DMF in both core and Sheath resulted in NFs within 50–160 nm along with large beaded structures. Addition of Trichloromethane (TCM) or Trifluoroethanol (TFE) in sheath turned NFs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 36 publications
2
37
1
Order By: Relevance
“…Polycaprolactone (PCL) is a biocompatible and biodegradable polymer frequently used for the preparation of nanoparticles . PCL degradation is slower than poly(lactic‐co‐glycolic acid) (PLGA), making it more appropriate for delivery of biologics.…”
Section: Introductionmentioning
confidence: 99%
“…Polycaprolactone (PCL) is a biocompatible and biodegradable polymer frequently used for the preparation of nanoparticles . PCL degradation is slower than poly(lactic‐co‐glycolic acid) (PLGA), making it more appropriate for delivery of biologics.…”
Section: Introductionmentioning
confidence: 99%
“…This is shown in particular for formulations with lower % DL. The initial burst could be due to the dissolution of drug molecules that are present at the surface of microspheres 14,19 .…”
Section: Particle Size and Morphologymentioning
confidence: 99%
“…Compared with polymeric nanosphere systems, these compositions could self-assemble into nanoparticles with drugs themselves as carriers (also referred to as "carrier-free"), which have higher drug loading efficiency and offer more stable drug release. 20,21 Previous studies have demonstrated that Ptx is a widely used model drug to achieve the "carrier-free" goal. 19,[22][23][24] As our previous study reported, Ptx loaded nanoparticles can be designed by the conjugation of Ptx and a small molecule compound, succinic acid (SA), with a very high drug loading content (90%).…”
Section: Introductionmentioning
confidence: 99%